Pengaruh Perbedaan Salinitas Terhadap Tingkat Osmoregulasi Larva Udang Vaname Penaeus vannamei - Atjo, Andi Arham; Anita; Januar Noor, Rahmat; Rusyd Mahfud, Chairul (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
This study aims to determine the effect of differences in salinity on the level of osmoregulation of vaname shrimp larvae (L. vannamei). The research method used a completely randomized design with 4 treatments and 3 replications, namely treatment 17 ppt (A), 22 ppt (B), 27 ppt (C), and 32 ppt (D). The parameters observed were survival rate, absolute weight growth, and osmoregulation at the osmotic work rate (TKO) of vaname shrimp. Data analysis used descriptive. A salinity of 22 ppt gave the best results for survival rates, namely 92.22%, and the best absolute weight growth results, namely 1.03 grams at a salinity of 17 ppt. The results showed that differences in salinity had no significant effect (p > 0.05) on survival and growth in absolute weight. The TKO value of treatment A is media with a salinity of 17 ppt with a value of 654 mOsm/H2O which is the highest TKO value and is a shrimp that is hyperosmotic, namely a liquid whose osmotic concentration is higher than its environment, treatment B is a medium with a salinity of 22 ppt with a value of 500 mOsm/H2O which is the lowest TKO value and is a shrimp that includes isoosmotic regulation. The level of osmoregulation in vaname shrimp indicates a stagnant osmotic performance level so it can be stated that there is no difference in TKO based on salinity.